Understanding forest degradation - a review of forest structure indicators / Alexius Korom ... [et al.] - Korom, Alexius; Syukur, Mohd Shahrizan; Jawan, Ajimi; Suratman, Mohd Nazip; Jalloh, Mohamadu Boyie; Jamian, Mohd Azizul Hafiz; Abd Latif, Zulkiflee (Universiti Teknologi MARA, Sabah, 2022)
Forest degradation has profoundly impacted the forest structure which has affected the carbon stock, biodiversity, microclimate and function of the ecosystem. This consequently reduces the forest's capacity in providing goods and services. Forest degradation is typically a multi-stage anthropological process that develops gradually but might be accelerated by phenomena such as forest fires, storms, landslides, or floods. Hence, identification of site-specific forest degradation is crucial in the forest management system. Unlike deforestation, estimating the carbon emission from forest degradation is challenging due to the difficulty in defining the motive of degradation itself. Under the Reducing Emissions from Deforestation and Forest Degradation-plus (REDD+) framework, it is important to measure the changes in forest structure. This study discusses a few related forest structure indicators in assessing forest degradation such as the canopy cover, aboveground biomass and stand structure. To understand forest degradation, it is necessary to understand the forest structure indicators which could contribute to establishing a better forest management system.